Metode Tafsir Al-Qur’an - Hakmi Hidayat; Diva Kurnia Dwi S; Nur Rahmawati Wahid; Nasywa Kamila Putri (CV. ITTC INDONESIA, 2024)
The method of interpreting the Qur'an is a scholarly approach to understanding and explaining the meanings of the Qur'anic verses. Key methods include tafsir bil ma'thur, which is based on the traditions of the Prophet and his companions; tafsir bil ra'yi, which employs logical reasoning and critical thinking; thematic tafsir, which studies verses based on specific themes; and tafsir tahlili, which provides a detailed analysis of each word. Each method has its own strengths and challenges, but all aim to uncover deeper and more relevant meanings of the Qur'anic text. By combining various approaches, Qur'anic interpretation can offer a comprehensive and practical understanding for Muslims and address contemporary issues. These diverse methods ensure that the messages of the Qur'an remain relevant and applicable in different social and cultural contexts